Raising double-muscled breed cattle and their crossbreds in the tropics: insight from growth models - Abdullah, Ummi Noorhakimah; Meng, Goh Yong (Veterinary World, 2024)
Background and Aim: In tropical conditions, modeling the predictive parameters of live weight, including those at birth, pre-weaning, post-weaning, finishing, and maturing, and the average daily gain, is challenging. The heat load significantly influences the growth rate and final mature weights in the tropics. The study compared the growth rates of Kedah-Kelantan (KK), Brahman (BRAH), and Belgian Blue (BB) crossbred calves. Materials and Methods: The study conducted growth analysis using the non-linear regression growth models as it approximates the sex, breed, and growth physiology changes in beef cattle. It is supported by the utility of the most common growth functions (Brody, Logistic, von Bertalanffy, and Richard’s model) in normal-muscled tropical breeds and double-muscled crossbred beef cattle in the tropics. Results: The BB crossbreds outperformed the KK and BRAH breeds by 50%–100% in live weight gains under tropical conditions. The crossbreds display the double-muscled effect and highlight the advantages of heterosis, making them suitable for upgrading local herds. The study’s findings on the growth characteristics of BB crossbred cattle were best described by the von Bertalanffy growth model, which had a high coefficient of determination (R2 > 0.8) and yielded estimated mature weights of 527.5 kg for males and 518.5 kg for females. Conclusion: According to results, raising BB crossbreds in the tropics as a solution to ensure a sustainable beef supply could yield significant growth and economic benefits.